Patients Having Major Abdominal Cancer Surgery Exhibit Significant Acute Muscle Wasting - Gabor Dudas; Ismita Chhetri; Martin Whyte; Margaret Rayman; Rachel Simmonds; Anthony Catchpole; Mark Griffiths; Ben Creagh‐Brown (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Postoperative myopenia (acute muscle loss) is a significant concern following major cancer resection surgery, contributing to prolonged recovery, increased dependency and impaired quality of life. Despite its clinical relevance, the mechanisms underlying postoperative myopenia and its potential mediators remain poorly understood. This study aims to evaluate the acute changes in muscle size, strength and activity following major cancer surgery and to explore the role of insulin resistance and selenium deficiency as potential mediators of these alterations. Methods A prospective cohort study was conducted involving 52 patients undergoing elective open major abdominal surgery for cancer. Preoperative and postoperative assessments included measurements of rectus femoris cross‐sectional area (RFCSA) via ultrasound, handgrip strength (HGS), sniff nasal inspiratory pressure (SNIP) and physical activity using an accelerometer. Blood samples were analysed for markers of muscle metabolism, systemic inflammation, insulin resistance and selenium levels. Statistical analyses were performed to compare preoperative and postoperative values and to explore correlations between these measures and clinical outcomes. Results A significant reduction in RFCSA was observed in 50% of patients, with a median decrease of 10.2% within the first week post‐surgery, which persisted at the 6‐week follow‐up. HGS and SNIP also showed significant declines postoperatively, and reduced physical activity was associated with greater muscle loss. Insulin resistance and postoperative selenium depletion were associated with greater reductions in RFCSA. Conclusion Major cancer surgery is associated with significant acute muscle loss, which is not fully recovered by 6 weeks postoperatively. Insulin resistance and selenium deficiency may contribute to this muscle loss. Further research is needed to investigate potential interventions to prevent or mitigate postoperative myopenia.